1967
DOI: 10.1128/am.15.1.35-42.1967
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Relative Humidity on the Survival of Some Airborne Viruses

Abstract: A system for studying the effects of relative humidity (RH) and temperature on biological aerosols, utilizing a modified toroid for a static aerosol chamber, is described. Studies were conducted at 23 C and at three RH levels (10, 35, and 90%) with four viruses (Newcastle disease virus, infectious bovine rhinotracheitis virus, vesicular stomatitis virus, and Escherichia coli B T3 bacteriophage). Virus loss on aerosol generation was consistently lower at 90% than at 10 or 35% RH. When st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Below the ERH, the reaction no longer occurs in solution, and so inactivation may be slower. The non-monotonic (‘U-shaped’) dependence of virus inactivation on relative humidity, observed in our data ( Figure 1a ) and elsewhere in the literature ( Yang et al, 2012 ; Benbough, 1971 ; Prussin et al, 2018 ; Webb et al, 1963 ), including for coronaviruses ( Casanova et al, 2010 ; Songer, 1967 ), could be explained by this regime shift around the ERH ( Figure 1c ).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Below the ERH, the reaction no longer occurs in solution, and so inactivation may be slower. The non-monotonic (‘U-shaped’) dependence of virus inactivation on relative humidity, observed in our data ( Figure 1a ) and elsewhere in the literature ( Yang et al, 2012 ; Benbough, 1971 ; Prussin et al, 2018 ; Webb et al, 1963 ), including for coronaviruses ( Casanova et al, 2010 ; Songer, 1967 ), could be explained by this regime shift around the ERH ( Figure 1c ).…”
Section: Resultssupporting
confidence: 71%
“…Combining novel data, mathematical modeling, and a meta-analysis of existing literature, we have developed a unified, mechanistic framework to quantify the joint effects of temperature and humidity on virus stability. In particular, our model provides a mechanism for the non-linear and non-monotonic relationship between relative humidity and virus stability previously observed for numerous enveloped viruses ( Yang and Marr, 2012 ; Casanova et al, 2010 ; Songer, 1967 ), but not previously reported for SARS-CoV-2. Our work documents and explains the strong dependence of SARS-CoV-2 stability on environmental temperature and relative humidity, and accurately predicts half-lives for five coronavirus species in conditions from 4°C to 95°C, and from 30% to 80% RH and in bulk solution.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Animal studies have shown that influenza virus transmission is favored at low RH ( 135 , 137 ); however, a study of the 2009 pandemic influenza A virus (H1N1) in more physiologically realistic medium reported that the virus remained highly stable and infectious over a broad RH range between 20 and 100% ( 138 ). A study investigated the sensitivity of 11 airborne viruses to RH and found that although some RNA viruses survived best at low RH, other viruses survived better at high RH ( 139 ). The relationship between RH and virus viability in droplets and aerosols is characteristic to the virus, modulated by both the intrinsic physicochemical properties of the virus and its surrounding environment ( 113 , 129 , 139 ) ( Fig.…”
Section: Environmental Factors That Affect Aerosol Transmissionmentioning
confidence: 99%